Grass Functional Traits Differentiate Forest and Savanna in the Madagascar Central Highlands - Solofondranohatra, Cédrique L.; Vorontsova, Maria S.; Hackel, Jan; Besnard, Guillaume; Cable, Stuart; Williams, Jenny; Jeannoda, Vololoniaina; Lehmann, Caroline E. R. (Frontiers in Ecology and Evolution, 2018)
Grassland, woodland and forest are three key vegetation types that co-occur across the central highlands of Madagascar, where the woodland has historically been considered as degraded forest. Here, we use grass functional traits to inform our understanding of the biogeography of Malagasy vegetation and the differentiation of vegetation types in the region. We sampled grass community composition at 56 sites across the central highlands of Madagascar spanning grassland, woodland and forest. We selected seven functional traits known to correlate with different aspects of life history collated via GrassBase (habit, culm type, physiology, leaf consistency, plant height, leaf width and leaf length) for the 71 constituent species. Via analyses of the beta diversity, rank abundance, functional dispersion, functional group richness and community phylogenetic structure of grassland communities, we differentiate these vegetation types using plant functional traits. Grassland and woodland are highly similar in grass species composition and dominated by the same species (Loudetia simplex, Trachypogon spicatus and Schizachyrium sanguineum). In contrast, forest grass species composition significantly differs from both grassland and woodland. Consistent with these species composition patterns, the vegetation types can be distinguished based on physiology, culm type and leaf consistency. Forests harbour primarily C3 grasses, which are almost invariably laterally spreading with herbaceous leaves. In contrast, both grassland and woodland species are predominantly tall, caespitose C4 grasses with coriaceous leaves. Forest grasses are phylogenetically clustered and less diverse than the grassland and woodland communities. Further, we sampled bark thickness of the common woody species occurring in the woodland and forest of the region and found that the relative bark thickness of the woodland tree species was significantly greater than that of forest species from the same genus. We found that the functional traits and architecture of grasses diverge strongly between forest and the grassland-woodland mosaic. We conclude that the woodlands, primarily dominated by Uapaca bojeri Baill., are a form of savanna and not forest as has been previously suggested.